THE IMPORTANCE OF THE SPECTROPHOTOMETRIC ANALYSIS METHOD IN THE STUDY OF THE COMPOSITION OF SUBSTANCES - Ibodulloeva M.I; Misirova Z.M. (International Journal of Innovations in Engineering Research and Technology, 2024)
This article discusses the importance of the spectrophotometric analysis method, one of the physico-chemical analyses, for studying the composition of substances.